Still city : poems - Maksymchuk, Oksana (PIttsburgh, PA : University of Pittsburgh Press, 2024)
First-Hand and Documentary Poetic Witness to the War in Ukraine.
Description based upon print version of record.
Description based on online resource; title from digital title page (viewed on October 01, 2024).
JSTOR
Keywords: Russo-Ukrainian War, 2014- -- Poetry; War and society -- Poetry; War -- Psychological aspects -- Poetry; Ukraine -- Poetry; Ukrainian American poetry -- 21st century; Guerre et société -- Poésie.; Guerre -- Aspect psychologique -- Poésie.; Russian & Former Soviet Union; Death; Subjects & Themes; Places; Women Authors; poetry; Poetry; Poésie.; Electronic books